Nitrogen availability under conventional and conservation tillage in semiarid Inceptisol - YADAV, SURYA P; KUMAR, SARVENDRA; DAS, T K; PURAKAYASTHA, T J; SHARMA, V K; BHATTACHARYYA, R; BANDYOPADHYAY, K K; G, ROSIN K; VISHWANATH, VISHWANATH (The Indian Journal of Agricultural Sciences, 2021)
The present experiment was conducted to study the spatio-temporal variation of available nitrogen fraction in cotton (Gossypium hirsutum L.) in conservation agricultural based long term experiment (since 2010) during 2019-20. The treatment comprises two distinct practices, i.e. conventional tillage (CT) and zero tillage (ZT). Under ZT, permanent narrow bed without (PNB) and with residue of previous crops (PNB+R); permanent broad bed without (PBB) and with residues (PBB+R); flat bed (FB) and FB with residues (FB+R). Soil samples were collected (0-15 and 15-30 cm) at pre-flowering, flowering, boll formation and harvest stages. Adoption of CA practices increased the NH4-N, NO3-N and mineral-N fractions of nitrogen at different crop growth stages. Highest NH4-N, NO3-N and mineral-N were recorded at flowering and boll formation stage respectively. The effect of crop residue retention and crop establishment methods on available N fractions was prominent up to 15 cm soil depth. Crop residue retained plots recorded significantly higher N fraction compared to respective without residue and CT plots. Residue retained plots of FB, PBB, PNB recorded 50, 25 and 36% higher NO3-N concentration as compared to respective without residues plots at pre-flowering stage. At flowering stage, maximum NH4-N was recorded in PBB+R (17.9 mg/kg) and FB+R plots (17.5 mg/kg), which was approximately 68 and 16% higher over CT and PNB+R plots. The results revealed that zero tillage together with PBB+R could be a viable option over conventional practice for maintaining nitrogen availability to plants under cotton-wheat (Triticum aestivum L.) cropping system in semiarid climate.